Gamification as a challenging response to motivate classes in secondary education in the context of COVID-19 (Revista Innova Educación, 2021)
The objective was to determine the correlation between gamification and motivation. It was developed through quantitative, non-experimental and correlational research. We worked with a census population of 253 students of regular basic education. To obtain data, the Gamification Observation Guide by García (2020) and the MSLQ Motivation Questionnaire by T. García et al. (1988). The results indicated that there is a very low, significant relationship of 0.025 (p value = 0.0694> 0.05). It is concluded that gamification is not related to the motivation of the students, most of the teachers, in the development of their classes, do not use digital tools - a necessary element in the delivery of classes at a distance and virtually due to the difficult situation caused by COVID-19. Likewise, teachers suffer from inexperience in handling social networks, videoconferences and online forms.
Keywords: digital skills; COVID-19; gamification; motivation; pandemic; education; secondary education